2020
DOI: 10.3390/app11010232
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Olive Leaves’ Surface by Ultrasound Cavitation. Correlation with Polyphenol Extraction Enhancement

Abstract: We investigated the impact of ultrasound at 20 kHz on olive leaves to understand how acoustic cavitation could increase polyphenol extraction. Application of ultrasound to whole leaf from 5 to 60 min enabled us to increase extraction from 6.96 to 48.75 µg eq. oleuropein/mL of extract. These results were correlated with Environmental Scanning Electron Microscopy, allowing for leaf surface observation and optical microscopy of treated leaf cross sections to understand histochemical modifications. Our observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…From the practical point of view, using sonication in the preparation of the oil systems could improve the transfer of antioxidants from both EWS to the oils. In this regard, several authors have reported the enhancement of the antioxidant capacity and the preservation of bioactive compounds in the matrix (Abid et al, 2014;Guerrouj et al, 2016;Riciputi et al, 2018;Rombaut et al, 2020) when using this emerging technology, because it allows obtaining a more homogeneous distribution of bioactive compounds inside to samples thanks to the formation of bubbles during the cavitation process (Amirante et al, 2017;Shanmugam & Ashokkumar, 2015). In addition, the polyphenol compounds extracted from a sonication process have shown a higher antioxidant potential (Dzah et al, 2020).…”
Section: Determination Of the Oxidative Stabilitymentioning
confidence: 99%
“…From the practical point of view, using sonication in the preparation of the oil systems could improve the transfer of antioxidants from both EWS to the oils. In this regard, several authors have reported the enhancement of the antioxidant capacity and the preservation of bioactive compounds in the matrix (Abid et al, 2014;Guerrouj et al, 2016;Riciputi et al, 2018;Rombaut et al, 2020) when using this emerging technology, because it allows obtaining a more homogeneous distribution of bioactive compounds inside to samples thanks to the formation of bubbles during the cavitation process (Amirante et al, 2017;Shanmugam & Ashokkumar, 2015). In addition, the polyphenol compounds extracted from a sonication process have shown a higher antioxidant potential (Dzah et al, 2020).…”
Section: Determination Of the Oxidative Stabilitymentioning
confidence: 99%
“…Ultrasound contributes to high-frequency vibrations that cause cavitation in the liquids. Due to the high penetration effect, it can transmit powerful energy [ 45 ]. The energy increases the bonding probability when the substrate and enzymes interact.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3k–l, normal integrity of cell walls and aligned structure is visible in two SEM figures with two magnifications. In Figure 3a,b, leaves that extracted with ethanol, due to penetration of solvent into the leaf structure, the cell walls are reduced in elongation and density, and the space between them is increased (Rombaut et al., 2021). In other words, the cell walls have been tilted under ultrasonic waves.…”
Section: Resultsmentioning
confidence: 99%